Using Open Science Tools to Teach Environmental Sciences - Mario Zuliani; C. J. Lortie (Ecology and Evolution, 2025)
ABSTRACT Open science, work and knowledge that are developed in full, offers critical resources that provide students with insights into the process of research in many fields. There are extensive opportunities within environmental sciences to incorporate open science into undergraduate level courses. There are seven major open science concepts that could be used to teach undergraduate environmental science courses that align with professional research activities, including open‐access papers, pre‐prints, open data, open‐source software, published code, collaborative tools for version control, and open notebooks. Here, we assessed the use of these open science concepts in connection to the European Union pillars of open science, outlining key benefits, challenges, and how these tools can be used in undergraduate environmental science courses. Specifically, these tools support a framework for open science structured around eight pillars, providing incentives to collaborate, enhancing transparency and openness, and promoting diversity and inclusivity. Collectively, these tools support teaching environmental science content as many of the skills gained directly relate to analyzing environmental topics and data while supporting transparency to collaborators and stakeholders. This provides learning opportunities including finding and reusing data, team collaboration, and reading and working with code. Further endorsing the use of open science in environmental science courses can enhance these courses as these tools align with professional research activities that are currently being used, including publishing data collected in labs, pre‐print publishing capstone papers or lab reports, openly publishing code used for analysis, and publishing field notes.